Development of a Batak Culture-Based School Management Model as an Effort to Increase Cooperation and Active Participation of Stakeholders School Effectively and Efficiently in Elementary School and Intermediate in the District of Si Empat Nempu Hilir Regency of Dairi - Dionisius Sihombing; Albert Pauli Sirait; Mangido Nainggolan (Jurnal Multidisiplin Madani, 2022)
The purpose of this research is to produce a model that is used as a reference to improve cooperation and participation active stakeholders Elementary and secondary schools in Si Empat Nempu Hilir District, Dairi Regency. Method used is research and development method with stages developed by Borg and Gall.  This research will produce Model Management school and Book Guidelines application model. This model will be tested in three stages, namely: the test stage try, Step main and Step operational, with involve school and stakeholders in primary and secondary schools. The analytical technique that the researcher uses is statistical analysis with a qualitative approach and quantitative. Researcher hope that model MSB3 could increase cooperation and participation active stakeholders in advance school in Si Empat Nempu Hilir, Dairi Regency